SURPRISING ENERGY FUTURES : Neo-Carbon Energy Futures Clinique V - Heinonen, Sirkka; Karjalainen, Joni; Parkkinen, Marjukka; Ruotsalainen, Juho; Zavialova, Sofia; Kurki, Sofi; Laurén, Leena-Maija; Salminen, Hazel; Taylor, Amos (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
This report describes the process and results of futures clinique Surprising Energy Futures: Anticipating Discontinuities and Testing Resilience of Renewable Energy World with Black Swans, held on 17 May 2017 at Sitra, Helsinki. The event was the fifth futures clinique within the foresight part of the research project Neo-Carbon Enabling Neo-Growth Society – Transformative Scenarios 2050, conducted by Finland Futures Research Centre. The aim of the event was to contribute to the four transformative societal scenarios of Neo-Carbon Energy project. The event consisted of presentations and intermittent working sessions. Dr. Karlheinz Steinmüller discussed the topic of Black Swans and VUCA World, with comments by Prof. Jarno Limnéll.